Machining Accuracy Enhancement of a Machine Tool by a Cooling Channel Design for a Built-in Spindle - Kun-Ying Li; Win-Jet Luo; Shih-Jie Wei (Applied Sciences, 2020)
This study presents a multiphysics simulation analysis that was performed for the cooling channel of a built-in spindle. The design of experiments (DOE) method was employed to optimize the dimension of the cooling channel, and a practical machining experiment was performed to validate the effect of the design. In terms of the temperature, pressure drop, thermal deformation, manufacturing cost, and initial cost considerations, the paralleling type cooling channel of the front bearing and the helical type cooling channel of the motor were adopted in the study. After the optimal design of the cooling channel was applied, the bearing temperature was reduced by a maximum decrease of 6.7 °C, the spindle deformation decreased from 53.8 μm to 30.9 μm, and the required operational time for attaining the steady state of the machine tool was shortened from 185.3 min to 132.6 min. For the machining validation, the spindle with the optimal cooling channel design was employed for vehicle part machining, the flatness of the finished workpiece was increased by 61.3%, and the surface roughness (Ra) was increased by 52%. According to the findings for the optimal cooling channel, when the spindle cooling efficiency is increased by the optimal cooling channel design, the thermal deformation and warm-up period can be reduced effectively, and the machining precision can be enhanced. This method is an efficient way to increase the accuracy of a machine tool.